Post-disaster recovery processes in neoliberal biopolitics contexts: The cases of Chile (2010) and Brazil (2011) - Juan Saavedra; Victor Marchezini (Íconos)
This article makes a comparative analysis between two post-disaster normality recovery processes under the neoliberal governmentality. The first case is the earthquake-tsunami which took place on February 27, 2010 in the center-south area of Chile and the second case is of the flooding and landslide on Janu-ary 12, 2011 in the Serrana region in Rio de Janeiro, Brazil. The analysis was made through revisions of documentary sources about these cases and field work, and qualitative interviews. The long-term recovery processes, the conditions of insecurity in the dimensions of social life and the challenges for professionals working in the neoliberal biopolitics context were examined through analytical categories. The results of this comparative analysis allow us to observe that disasters are social and historical processes that occur in contexts of political regimes in both countries (neoliberal) with a resolution that alludes to mechanisms and instruments of biopolitics. This last point has implications for different dimensions of government focused on emergency, such as the administration of life where gender issues are relevant.